Contribution of legislative infrastructure for participative banking to activating real financial inclusion in Algeria - Hamou, Abdellah; Hakmi, Nadjib Allah; Magoura, Khaled; Benguettaf, Mohamed; Imansouren, Souhila (The International tax journal, 2025)
This study aims to explore the extent to which the legislative structure of Participative banking contributes to real financial inclusion in Algeria. Most previous literature has focused on studying the positive impact of Participative banks on financial inclusion. The study contributed to uncovering the key to expanding the concept of Participative banking through legislation based on the availability of guarantees for all parties involved in financial transactions, particularly Regulation No. 18-02, Regulation 20-02, and the Monetary and Credit Law 23-09. The study demonstrated how these laws contributed to expanding the scope of real financial inclusion (deposits), given the extensive exploitation of these laws by private banks in terms of the number of branches and even the percentage of financing in the form of deposits. It was found that there is a significant correlation between bank deposits and the size of branches, reflecting the interconnectedness, responsiveness, and widespread use of all available Participative banking services, thus achieving the goal of real financial inclusion through the legislative infrastructure.